Acu-TENS Reduces Breathlessness during Exercise in People with Chronic Obstructive Pulmonary Disease. (20th February 2017) - Ngai, Shirley P. C.; Spencer, Lissa M.; Jones, Alice Y. M.; Alison, Jennifer A.
Abstract : Background. Exertional dyspnoea limits level of physical activity in people with Chronic Obstructive Pulmonary Disease (COPD). This randomized, double-blinded, crossover study evaluated the effect of Acu-TENS, application of Transcutaneous Electrical Nerve Stimulation on acupoints, on breathlessness during exercise in people with COPD. Methods. Twenty-one participants, mean% predicted FEV1 50 ± 21 %, attended assessment followed by two intervention days, one week apart. On each intervention day, participants performed two endurance shuttle walk tests (ESWT) (Walk 1 and Walk 2). Walk 1 was performed without intervention and Walk 2 was performed with either Acu-TENS or Sham-TENS, in random order, for 45 minutes before and during Walk 2. Duration of each ESWT and dyspnoea score at isotime of Walk 1 and Walk 2 on each intervention day were compared. Between-group differences in ESWT duration and isotime dyspnoea were also compared. Results. At isotime of Walk 1 and Walk 2, Acu-TENS showed significant reduction in dyspnoea of −0.8 point (95% CI −0.2 to −1.4) but not in Sham-TENS [0.1 point (95% CI −0.4 to 0.6)]. Compared to Sham-TENS, Acu-TENS showed significant reduction in dyspnoea of −0.9 point (95% CI −0.2 to −1.6) while no between-group significance was found in ESWT duration. Conclusion. Acu-TENS alleviated dyspnoea during walking in people with COPD but did not increase walking duration.